Modelos lineares generalizados mistos na avaliação genética da prenhez precoce na raça Nelore - Garcia, D. A. [UNESP]; Pereira, I. G.; Fonseca e Silva, F.; Pires, A. V.; Pessoa, M. C. [UNESP]; Oliveira, R. A. M. (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 2012)
This study aimed to use the generalized linear models with probit and logit link function to evaluate early pregnancy, and to observe the effects on genetic variability and on sire selection when different ages are adopted in the definition of this trait. Early pregnancy was studied at 15 (EP15), and 21 (EP21) months. The analysis was done in R software. Pearson correlations (PC), between genetic predicted values and percentage of bulls in common considering only 10% of bulls with higher genetic values (TOP 10), between classification by logit and probit models and in each model among EP15 and EP21, were calculated. The heritability for EP15 and EP21 were close between models, except for EP15 using probit link function. PC and TOP10 among models were high. The Akaike and Bayesian criteria reported was similar between models. TOP10, considering the same model, among EP15-EP21 were moderated between EP15-EP21.
Generalized linear mixed models on genetic evaluation of early pregnancy in Nellore breed
Keywords: beef cattle heritability; early pregnancy; link function